Proposed Methodology for Knowledge Acquisition: A Study on Congenital Heart Disease Diagnosis - Leãot, F. B.; Rocha, F. A. (Methods of Information in Medicine, 1990)
“Knowledge and human power are synonymous, since the ignorance of the cause frustrates the effect:…“Francis Bacon1This paper proposes a methodology for knowledge acquisition (KA) from multiple experts, in an attempt to elicit the heuristic rules followed by the physician in diagnosing twelve frequently occurring congenital heart diseases (CHD). Twenty-two pediatric cardiologists and twenty-three general cardiologists were interviewed with this technique; 274 interviews were conducted, 169 with the 22 experts, 105 with the 23 non-experts. A graph formalism was employed to represent their reasoning model, leading to the construction of a “mean reasoning model” for each diagnosis, separately for experts and non-experts. The results indicate that experts, compared to non-experts, tend to build knowledge representation models (KRM) that are smaller and less complex. Qualitative differences in information utilization between the two groups were also observed. Entropy analysis suggests a greater objectivity and cohesion of the experts’ model.
Keywords: Knowledge Acquisition; Expert Systems; Heuristic Learning; Reasoning Models